The Role of Aqidah Akhlaq Teachers in Shaping the Character of Grade VIII Students at MTs Ma'arif 31 Tri Bhakti Sido Makmur East Lampung - Aprizal, Aprizal; Irhamudin, Irhamudin; Abrori, M.Sayyidul (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
In the context of education, leadership is characterized by the commitment and professional work of teachers or educators, encompassing various aspects such as teaching, mentoring, and character development of students. This study explores the factors considered by teachers in developing the character of eighth-grade students at MTs Ma’arif 31 Tri Bhakti Sido Makmur, East Lampung. Teachers, especially those who are new to the profession, must first cultivate their own character, as they serve as role models and exert a direct influence on their students through their attitudes and behaviors. The process of character formation is carried out both inside and outside the classroom using several educational methods, including the Exemplary Method (al-Uswah al-Hasanah), the Habituation Method (Ta‘widiyyah), the Advice and Counsel Method (Mau‘izhah wa al-Nasehah), and the Reward and Punishment Method (‘Iqab). These approaches aim to help students understand and internalize moral and ethical values as part of the school’s character education program—initiated and exemplified by the teachers themselves. This study contributes to the understanding of how teachers’ self-character formation and pedagogical strategies synergize to build students’ moral character. It offers a practical framework for educators and institutions seeking to implement effective character education through Islamic-based pedagogical methods.